PENGARUH GENDER, KOMPETENSI PROFESIONAL, PENGALAMAN AUDITOR TEHADAP AUDIT JUDGMENT DI KANTOR AKUNTAN PUBLIK PROVINSI BALI - Ni Wayan Ayu Nola Widiyanti; I Putu Nuratama (Hita Akuntansi dan Keuangan, 2021)
This study aims to analyze the influence of gender, professional competence, and auditor experience on audit judgment at the Public Accounting Firm (KAP) in Bali Province. This study uses primary data obtained by distributing questionnaires to auditors who work at the Public Accounting Firm (KAP). The number of samples in this study were 63 auditors who work at the Public Accounting Firm (KAP) in Bali Province. The sample in this study was determined by purposive sampling method. The data analysis technique in this study used multiple linear regression analysis. In addition, all variables have been tested using the classical assumption test. The results showed that gender has no influence on audit judgment. Which means that there is no difference between female and male auditors in producing judgment. Professional competence has a positive and significant effect on audit judgment. Which means that the more competent an auditor is, the better the resulting audit judgment will be. Auditor experience has a positive and significant effect on audit judgment. Which means that an experienced auditor can produce a more precise audit judgment.